Dynamic Natural Monopoly Regulation: Time Inconsistency, Moral Hazard, and Political Environments - Lim, Claire S. H.; Yurukoglu, Ali (Journal of Political Economy, 2018)
This paper quantitatively assesses time inconsistency, moral hazard, and political ideology in monopoly regulation of electricity distribution. We specify and estimate a dynamic model of utility regulation featuring investment and moral hazard. We find underinvestment in electricity distribution capital aiming to reduce power outages and use the estimated model to quantify the value of regulatory commitment in inducing greater investment. Furthermore, more conservative political environments grant higher regulated returns but have higher rates of electricity loss. Using the estimated model, we quantify how conservative regulators thus mitigate welfare losses due to time inconsistency but worsen losses from moral hazard.